THE EFFECT OF LEVERAGE, INSTITUTIONAL OWNERSHIP, AND PROFITABILITY ON TAX AVOIDANCE WITH COMPANY SIZE AS A MODERATING VARIABLE IN HEALTHCARE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE 2021 – 2023 PERIOD - Dewi Rahmahwati; Sifa Widiyana; Shafira Cahyani Wulandari; Mohamad Zulman Hakim; Seleman Hardi Yahawi; Wati Yaramah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study intends to understand the impact of Leverage, Institutional Ownership and Profitability on Tax Avoidance through Company Size as a moderation variable. The population of this study is Healthcare Companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The population is 33 companies using the purposive sampling method with 15 companies that meet the requirements, with a large amount of observation data of 45 data. This data study uses the method of combined data regression analysis through the E-views 12.0 program. The findings of the study prove that Leverage and Profitability have a negative impact on Tax avoidance. Institutional ownership has a positive impact on tax avoidance. Company Size can moderate the impact of Leverage, Institutional Ownership and Profitability on Tax avoidance.